Efficacy and safety of TNF antagonists in ocular sarcoidosis: data from the French registry STAT - Marquet, Alicia; Chapelon-Abric, Catherine; Maucort-Boulch, Delphine; Cohen-Aubart, Fleur; Pérard, Laurent; Bouillet, Laurence; Abad, Sébastien; Biellefeld, Philip; Bouvry, Diane; André, Marc; Noël, Nicolas; Bienvenu, Boris; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
Backgroung: This study investigated the efficacy and safety of TNF antagonists in sarcoid uveitis in unselected cases. Design: This is a multicentre study on patients with sarcoidosis who received TNF antagonists in pneumology and internal medicine departments in France. We present here the subgroup of patients with biopsy-proven sarcoid uveitis included in the nationwide registry STAT (Sarcoidosis treated with TNF AnTagonists). Results: Among the 132 patients included in this multicenter study, 18 patients with refractory uveitis were treated as a first-line TNF antagonist with infliximab (n=14), adalimumab (n=3) and certolizumab (n=1). Before anti-TNF initiation, the median duration of sarcoidosis was 42 months and 83% of the patients have been treated with at least one immunosuppressive drug. Six patients switched for a second-line TNF antagonist. After a mean time under treatment of 29 months, the treatment resulted in a significant decrease of the ophthalmic extrapulmonary Physician Organ Severity Tool (ePOST) (mean score: 4.2 vs. 2.6) scores and a steroid sparing effect (29.4±20.7 vs. 6.2±5.2 mg/d). Overall, the ophthalmic response, either complete or partial, was 67%. Nine patients (50%) presented adverse events, including severe infectious complications in 5 patients, which required anti-TNF treatment interruption in 6 cases (33%). Among the 7 responder patients who discontinued anti-TNF therapy, 71% relapsed. Finally, 12 patients (67%) could continue TNF antagonist treatment. Conclusions: TNF antagonists were efficient in 67% of biopsy-proven refractory sarcoid uveitis. Severe adverse events, mainly infectious complications, were frequent. The high frequency of relapses after anti-TNF-α discontinuation requires a close patient follow-up thereafter.